Potential protective effects of ursolic acid against gamma irradiation-induced damage are mediated through the modulation of diverse inflammatory mediators - Wang, H.; Sim, M.; Loke, W.; Chinnathambi, A.; Alharbi, S.; Tang, F.; Sethi, Gautam (2017)
© 2017 Wang, Sim, Loke, Chinnathambi, Alharbi, Tang and Sethi. This study was aimed to evaluate the possible protective effects of ursolic acid (UA) against gamma radiation induced damage both in vitro as well as in vivo. It was observed that the exposure to gamma radiation dose- and time-dependently caused a significant decrease in the cell viability, while the treatment of UA attenuated this cytotoxicity. The production of free radicals including reactive oxygen species (ROS) and NO increased significantly post-irradiation and further induced lipid peroxidation and oxidative DNA damage in cells. These deleterious effects could also be effectively blocked by UA treatment. In addition, UA also reversed gamma irradiation induced inflammatory responses, as indicated by the decreased production of TNF-a, IL-6, and IL-1ß. NF-?B signaling pathway has been reported to be a key mediator involved in gamma radiation-induced cellular damage. Our results further demonstrated that gamma radiation dose- and time-dependently enhanced NF-?B DNA binding activity, which was significantly attenuated upon UA treatment. The post-irradiation increase in the expression of both phospho-p65, and phospho-I?Ba was also blocked by UA. Moreover, the treatment of UA was found to significantly prolong overall survival in mice exposed to whole body gamma irradiation, and reduce the excessive inflammatory responses. Given its radioprotective efficacy as described here, UA as an antioxidant and NF-?B pathway blocker, may function as an important pharmacological agent in protecting against gamma irradiation-induced injury.